Care Challenges Due to COVID-19 and Mental Health Among Caregivers of U.S. Adults With a Chronic or Disabling Condition. Issue 3 (6th October 2021) - Leggett, Amanda N; Carmichael, Alicia; Leonard, Natalie; Jackson, Jeannette; Kirch, Matthias; Solway, Erica; Kullgren, Jeffrey T; Singer, Dianne; Malani, Preeti N; Gonzalez, Richard
Abstract: Background and Objectives: The coronavirus disease 2019 (COVID-19) pandemic poses new challenges for caregivers of adults with chronic or disabling conditions. This study uses nationally representative data to examine the prevalence of pandemic care challenges and supports and their associations with caregiver mental health and interpersonal well-being. Research Design and Methods: Participants include 311 caregivers aged 50–80 in the United States who were providing care for an adult with a chronic or disabling condition from the June 2020 National Poll on Healthy Aging. Five care challenges (e.g., confusion on public health guidelines) and 2 supports (e.g., physician offered information on care during COVID-19) are treated as predictors of caregiver mental health (care-related stress, self-reported mental health, and depressive symptoms) and interpersonal well-being (interpersonal conflicts, lack of companionship, and isolation). Results: Each care challenge/support was endorsed by 13%–23% of caregivers. In adjusted models, difficulty getting needed medical care was associated with greater caregiver stress, depressive symptoms, and lower interpersonal well-being. All care challenges universally predicted greater caregiver stress. Caregiving supports were not independently associated with caregiver' mental health and interpersonal well-being. Discussion and Implications: Care challenges were associated with caregivers' mental health and interpersonal well-being during the early months of the pandemic. Some of these challenges may be attributed to changing public health guidelines and practices as the pandemic unfolded, whereas others are relevant to all care contexts (e.g., less support from family). Tools and supports for caregivers must consider both changing policies and care needs.